Technical efficiency of smallholder honey farmers in Jimma zone, Ethiopia - Hailemariam Legesse; Yadeta Bekele; Mulubrihan Bayissa; Tsega Lemma (RUDN Journal of Economics, 2020)
This study analyzes technical efficiency and determinants of the efficiency of honey production in the Gomma and Gera districts of the Jimma zone. The data were obtained from 194 randomly selected honey-producing smallholder farmers. A Cobb - Douglas stochastic frontier production analysis with the inefficiency effect model was used to estimate technical efficiency and identify the determinants of efficiency variations among honey farmers. The study showed that several hives and supplementary feeds positively and significantly influenced honey yield. This shows that there is room to increase honey productivity from the current level if farmers can efficiently use these input variables. The result further showed that there were differences in technical efficiency among honey producers in the study area. The discrepancy ratio, γ, which measures the relative deviation of output from the frontier level due to inefficiency, was about 84%. This implies that about 84% of the variation in honey output among the farmers was attributed to technical inefficiency effects. The estimated mean level of technical efficiency of honey producers was about 74%. This reveals that there is a possibility to increase the level of honey output by about 26% through exploiting the existing local practices and technical knowledge of the relatively efficient farmers. The education level of the farmer, landholding, income, extension contact, and training were found to determine technical efficiency significantly. Therefore, the concerned sector should focus on the above variables to enhance the technical efficiency of honey producers in the study area.